Study of the Effect of Different Building Material on Human Comfort: Case study in Naturally Ventilated Badminton Court - Tan, Kai En; Bin Idris, Ahmad Fu'ad (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The objective of this study was to determine the effects of building materials towards comfort temperature in natural ventilated badminton court. This study provides a reference for engineer to make decision for a right choice of materials selection for a badminton court at a conceptual design stage to provide thermal comfort for badminton player. By collecting data on 3 badminton court constructed of different materials which were zinc, half zinc and half concrete, and concrete to show the effects of materials on comfort temperature, and the comfort temperature was predicted through regression analysis on the graph of air temperature versus PMV. Based on the results for zinc material’s badminton court, the comfort temperature range was between 26.71℃ to 28.20℃ while for the half zinc and half concrete material’s badminton court, the comfort temperature range was between 25.06℃ to 27.86℃. Lastly, for concrete material’s badminton court, the comfort temperature range was between 24.30℃ to 25.01℃. The study has shown that in naturally ventilated residential buildings, the building materials affect the human comfort. This study clarifies that concrete with low thermal conductivity reduces heat transfer from outdoor to indoor.